Nomadic Justice? Restorative Justice on the Margins of Law - Woolford, Andrew John (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. The tensions within the restorative justice movement, which advocates for an alternative to conventional legal retributive practices, are discussed. The “marginal” status claimed by the majority of restorative justice proponents in relation to the criminal justice system, as well as their fear of cooptation, have little basis. A “transformative politics” of restorative justice, that challenges and alters the retributive norms of the criminal justice system without merely becoming its appendage, necessitates both a distancing from, and engagement with, the system.